Increase in occurrence of large glacier-related landslides in the high mountains of Asia - Jia Liu; Yuming Wu; Xing Gao (Scientific Reports, 2021)
Abstract Globally, a large number of glaciers are retreating due to global warming. Along with climate change, glacial melting has been identified as one of the main triggers of landslide activity in high mountain areas. Evaluations of the triggered mechanism alone do not provide comprehensive insight into the overall impact of glacier accumulation and ablation on landslide-induced denudation. To investigate recent trends, we built landslide and glacier datasets for the HMA using a Landsat time-series covering the past 21 years (1998–2018). Landslides that may have been caused by major earthquakes were identified and removed, leaving an inventory that is used to explore changes that may be related to climate change. Our results show a shift in the frequency–area distribution that indicates an increasing trend of large landslides in the HMA over the last decade. A decline in glacier area is associated with the increase in landslide area.